COMPARISON BAY LEAF (SYZYGIUM POLYANTHUM (WIGHT) WALP) EKSTRAKT WITH 400 MG AND 600MG DOSE ON LIPOPROTEIN(A) CONCENTRATION IN DYSLIPIDEMIC PATIENTS - Catur Prianwari, Dharma Lindarto & Santi Syafril (International Journal of Research Science and Management, 2019)
Introduction: Dyslipidemia is a risk factor for cardiovascular disease. While Hyper Lipoprotein (a) is the main and independent risk factor for cardiovascular disease and aortic valve calcification stenosis. Synthetic antidyslipidemia drugs such as statin, niacin, mipomersen, and PCSK921 inhibitors had no clear evidence to reduce Lp(a) levels. Bay leaf ekstrakt was reported to have efficacy in lowering cholesterol and triglyceride levels, and was expected to reduce Lipoprotein(a). Aim : to compare the effects of giving bay leaf ekstrakt at a dose of 400 mg and 600 mg to Lp (a) levels in dyslipidemia patients. Method: This study was prospective design using clinical trial study. Study group I (n = 15) and control group II (n = 15) were chosen with double blinded random sampling. Data were obtained lipid profile and Lp (a) from blood sample which was taken before and after 30 days therapy. Data was analysed using T-dependent test with SPSS and p < 0,05 were considered significant. Result: Lp (a) before therapy compared to after examination decreased in group I (25.52 + 31.36 vs 22.66 + 31.12) ng / dL; p = 0.001) and group II (27.81 + 33.79 vs 25.65+ 33.23) ng / dL; p value = 0.013), statistically significant in both group I and group II. The decrease in Lipoprotein (a) levels in group I was greater than in group II, and was statistikally significant (2.86 vs 2.17) mg / dL; p = 0.005). Conclusion: The used of bay leaves (Syzygium polyanthum) extract 2 x @ 200 mg for 30 days reduced the levels of Lp(a) greater than 2x300 mg, and statistically significant